SOSIALISASI EKSISTENSI TANAH ULAYAT DI DESA KUIMASI, KECAMATAN FATULEU, KABUPATEN KUPANG - Orpa J. Nubatonis; Yossie M. Y. Jacob; Siti Ramlah Usman; Darius Mauritsius; Chatryen M. Dju Bire (Jurnal Abdi Insani, 2023)
Land is one of the most needed investments from time to time. The demand for land is starting to show with the increasingly rapid human growth, while the land for land is not increasing. In de facto, there are still tribal lands in NTT, but the power of indigenous peoples over tribal lands is no longer fully because what was previously considered as shared land, as a result of the individualization process has changed to individual ownership, this is partly because there are no regulations governing the existence of indigenous peoples and customary land or customary land. The lack of protection for indigenous peoples in Kupang Regency not only means that it has not been recognized by the state but also causes the existence and wealth of indigenous peoples, including customary lands, to be vulnerable to various interests both from within the indigenous peoples themselves and pressure from outsiders. This Community Service activity aims to explain in detail the existence of customary land in Kupang Regency, how important and urgent it is to provide protection for customary law communities and what kind of protection mechanism from the state is considered appropriate to the current characteristics of the Kupang Regency customary law community. The method used in this activity is lecture and question and answer. The results of the activity showed that the community was very enthusiastic about hearing and listening carefully to the explanations presented by the resource persons so that interesting discussions ensued. Through this activity, the community also gains new knowledge related to the existence of customary land. From the results of this activity it can also be concluded that the implementation of the activity in general went well because of the collaboration with various parties in the target location, namely the Kuimasi Village Office, Fatuleu District, Kupang Regency and also the target community (participants namely village officials, community leaders and the community ) in Kuimasi Village, Fatuleu Sub-district, Kupang Regency really hopes for further socialization in the field of law.